ABDOMINAL PSEUDOCYST DUE TO VENTRICULOPERITONEAL SHUNT: AN UNCOMMON COMPLICATION OF A COMMON NEUROSURGICAL PROCEDURE - ALfallaj , Muath Ibrahim; Salati, Sajad Ahmad; Malik, Faiza Riaz (Sanamed, 2025)
For over a century, the ventriculoperitoneal shunt has been a standard neurosurgical procedure for treating hydrocephalus. However, this procedure is associated with a variety of complications. One uncommon but notable complication is the abdominal cerebrospinal fluid (CSF) pseudocyst. This pseudocyst is histologically characterized by a fibrous wall devoid of an epithelial lining, and its exact etiopathogenesis remains unclear. Patients with abdominal CSF pseudocysts often present with nonspecific symptoms, and treatment is tailored to each individual's clinical situation. This article reviews the epidemiology, etiopathogenesis, clinical characteristics, histology, imaging features, and available treatment options for abdominal CSF pseudocysts.
Keywords: Ventriculoperitoneal shunt; pseudocyst; neurosurgery; hydrocephalus; cerebrospinal fluid; shunt revision